DETERMINAN FAKTOR STRUKTUR MODAL PERUSAHAAN TAMBANG YANG TERDAFTAR DI BURSA EFEK INDONESIA - Beta Asteria (MANAJEMEN DEWANTARA, 2018)
This study aims to determine the influence of Current Ratio (CR), Asset Structure (SA), Profitability (ROE) and Company Size (SIZE) partially and simultaneously to the capital structure of mining companies listed in Indonesia Stock Exchange 2013-2016. The type of research data is secondary data in the form of financial statement data, published by Indonesia Stock Exchange. Technique is using purposive sampling. The data used is panel data. There are 14 companies as cross section data and time series for 4 years from year 2013-2016. Research samples are 56. Method analyze data use multiple regression with program of SPSS. The result of the research shows that: 1) Current Ratio (CR) has significant effect to Capital Structure (CS) of Mining Company listed in Indonesian Stock Exchange in 2013-2016, 2) Asset Structure (SA) has no significant effect to Capital Structure CS) Mining Companies listed on the Indonesia Stock Exchange in 2013-2016, 3) Company size (SIZE) significantly influence the Capital Structure (CS) of Mining Companies listed on Indonesia Stock Exchange in 2013-2016, 4) Return On Equity (ROE) has no significant effect on Capital Structure (CS) of Mining Companies listed on Indonesia Stock Exchange in 2013-2016 and 5) Current Ratio (CR), Asset Structure (SA), Profitability (ROE) and Company Size (RO) SIZE) simultaneously have a significant effect on the company's capital structure (CS). Â Keywords: Capital Structure, Current Ratio, Asset Structure, Return on Equity and Company SizeÂ